Differentiation Questions

Question Number 162924 by mnjuly1970 last updated on 02/Jan/22

$$\: \\$$ $$\:\boldsymbol{\phi}\:=\int_{\mathrm{0}} ^{\:\infty} \frac{\:{e}^{\:−{x}^{\:\mathrm{2}} } .\mathrm{ln}\left(\:{x}\:\right)}{\:\sqrt{{x}}}\:{dx}=\lambda\:\Gamma\left(\frac{\mathrm{1}}{\mathrm{4}}\right) \\$$ $$\\$$ $$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\lambda=?\:\:\:\:\:\:\:\:\:\:\:\:\:\blacksquare \\$$ $$\\$$

Answered by Lordose last updated on 02/Jan/22

$$\varnothing\:=\:\int_{\mathrm{0}} ^{\:\infty} \mathrm{x}^{−\frac{\mathrm{1}}{\mathrm{2}}} \mathrm{e}^{−\mathrm{x}^{\mathrm{2}} } \mathrm{ln}\left(\mathrm{x}\right)\mathrm{dx} \\$$ $$\varnothing\:\overset{\mathrm{x}=\mathrm{x}^{\frac{\mathrm{1}}{\mathrm{2}}} } {=}\frac{\mathrm{1}}{\mathrm{4}}\int_{\mathrm{0}} ^{\:\infty} \mathrm{x}^{−\frac{\mathrm{1}}{\mathrm{4}}+\frac{\mathrm{1}}{\mathrm{2}}−\mathrm{1}} \mathrm{e}^{−\mathrm{x}} \mathrm{ln}\left(\mathrm{x}\right)\mathrm{dx} \\$$ $$\varnothing\left(\mathrm{a}\right)\:=\:\int_{\mathrm{0}} ^{\:\infty} \mathrm{x}^{\mathrm{a}−\mathrm{1}} \mathrm{e}^{−\mathrm{x}} \mathrm{dx}\:=\:\boldsymbol{\Gamma}\left(\mathrm{a}\right) \\$$ $$\varnothing'\left(\mathrm{a}\right)\:=\:\int_{\mathrm{0}} ^{\:\infty} \mathrm{x}^{\mathrm{a}−\mathrm{1}} \mathrm{e}^{−\mathrm{x}} \mathrm{ln}\left(\mathrm{x}\right)\mathrm{dx}\:=\:\boldsymbol{\Gamma}\left(\mathrm{a}\right)\boldsymbol{\psi}^{\left(\mathrm{0}\right)} \left(\mathrm{a}\right) \\$$ $$\varnothing\:=\:\varnothing'\left(\frac{\mathrm{1}}{\mathrm{4}}\right)\:=\:\boldsymbol{\Gamma}\left(\frac{\mathrm{1}}{\mathrm{4}}\right)\boldsymbol{\psi}^{\left(\mathrm{0}\right)} \left(\frac{\mathrm{1}}{\mathrm{4}}\right) \\$$ $$\lambda\:=\:\boldsymbol{\psi}^{\left(\mathrm{0}\right)} \left(\frac{\mathrm{1}}{\mathrm{4}}\right) \\$$

Commented bymnjuly1970 last updated on 02/Jan/22

$${thanks}\:{alot}\:{sir}\:{lordose} \\$$

Answered by mathmax by abdo last updated on 02/Jan/22

$$\Psi=\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{e}^{−\mathrm{x}^{\mathrm{2}} } \mathrm{lnx}}{\:\sqrt{\mathrm{x}}}\mathrm{dx}\Rightarrow\Psi=_{\mathrm{x}=\sqrt{\mathrm{t}}} \:\:\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{e}^{−\mathrm{t}} \mathrm{ln}\left(\sqrt{\mathrm{t}}\right)}{\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{4}}} }\frac{\mathrm{1}}{\mathrm{2}}\mathrm{t}^{−\frac{\mathrm{1}}{\mathrm{2}}} \mathrm{dt} \\$$ $$=\frac{\mathrm{1}}{\mathrm{4}}\int_{\mathrm{0}} ^{\infty} \:\:\mathrm{e}^{−\mathrm{t}} \mathrm{lnt}\:\mathrm{t}^{−\frac{\mathrm{3}}{\mathrm{4}}} \:\mathrm{dt}\:\:=\frac{\mathrm{1}}{\mathrm{4}}\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{4}}−\mathrm{1}} \:\mathrm{e}^{−\mathrm{t}} \mathrm{ln}\left(\mathrm{t}\right)\mathrm{dt} \\$$ $$\mathrm{let}\:\Gamma\left(\mathrm{a}\right)=\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\mathrm{a}−\mathrm{1}} \:\mathrm{e}^{−\mathrm{t}} \:\mathrm{dt}\:\Rightarrow\Gamma^{\left(\mathrm{1}\right)} \left(\mathrm{a}\right)=\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\mathrm{a}−\mathrm{1}} \:\mathrm{lnt}\:\mathrm{e}^{−\mathrm{t}} \:\mathrm{dt}\:\Rightarrow \\$$ $$\Gamma^{'} \left(\frac{\mathrm{1}}{\mathrm{4}}\right)=\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{4}}−\mathrm{1}} \:\mathrm{e}^{−\mathrm{t}} \mathrm{ln}\left(\mathrm{t}\right)\mathrm{dt}\:=\psi\left(\frac{\mathrm{1}}{\mathrm{4}}\right)\:\Rightarrow \\$$ $$\int_{\mathrm{0}} ^{\infty} \:\:\frac{\mathrm{e}^{−\mathrm{x}^{\mathrm{2}} } \mathrm{lnx}}{\:\sqrt{\mathrm{x}}}\mathrm{dx}=\frac{\mathrm{1}}{\mathrm{4}}\psi\left(\frac{\mathrm{1}}{\mathrm{4}}\right) \\$$

Commented bymathmax by abdo last updated on 03/Jan/22

$$\mathrm{sorry}\:\:\frac{\Gamma^{'} \left(\frac{\mathrm{1}}{\mathrm{4}}\right)}{\Gamma\left(\frac{\mathrm{1}}{\mathrm{4}}\right)}=\psi\left(\frac{\mathrm{1}}{\mathrm{4}}\right)\:\Rightarrow\Gamma^{'} \left(\frac{\mathrm{1}}{\mathrm{4}}\right)=\psi\left(\frac{\mathrm{1}}{\mathrm{4}}\right).\Gamma\left(\frac{\mathrm{1}}{\mathrm{4}}\right) \\$$